The energetics and kinetics of H in δ-TiH2: Ab initio study - Tao Wang; Jie Li; Pan Dong; Qi Zhu; Jiao Jiao Zhou; Y.W. You; Xiang-Shan Kong (Nuclear Materials and Energy)
Titanium (Ti) hydrides are frequently utilized as neutron moderators and structural components in environments where neutrons are present. However, the presence of vacancies, which are created by neutron irradiation, has a considerable impact on the service performance of these materials. In order to gain insight into the underlying micro-mechanisms, a systematic ab initio study was conducted with the aim of understanding the dissolution and diffusion of hydrogen in δ-TiH2. The findings indicate that interstitial hydrogen atoms are energetically favorable to occupy the sites surrounded by four lattice-point hydrogen atoms, with a dissolution energy of 0.55 eV. It is energetically unfavorable for hydrogen atoms to accumulate at interstitial sites in δ-TiH2. It has been demonstrated that vacancies can provide favorable spaces for the dissolution of hydrogen. Single Ti vacancy can trap up to 6 H atoms, and the cumulative binding energy of 6 H atoms with a Ti vacancy reaches 1.31 eV. The chemical potential of hydrogen has considerable influence on the interactions among interstitial H atoms and that between vacancies and hydrogen atoms. Ultimately, the density of states and difference charge density were employed to elucidate the underlying mechanisms that govern the interactions between hydrogen and vacancies.